IKHFA’ “DWIPROSES FONOLOGIS dan KAIDAH FONOLOGINYA” - Faqihul Agus Anam (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2017)
This research aims to describe phonological processes (PP) of ikhfa, as object of Qur’anic Phonology, and the phonological rule of ikhfa by Generative Phonology approach. In addition, this aims to prove the duality of PP ikhfa too. The data are al-Hashmi’s data (2004) that is wrtitten in his theses. The goal of aplicated this model of data is keeping validity of data. The result shows that PP of ikhfa’ is the duality of PP, namely consonant asimilation and vocalic nasalitation. The PP rule of PP ikhfa’ is [n] à/n/ [α ant] [β cor]/_ [α ant]. It means that arabic nasal sound [n] can be pronounced as phonem /n/ with [+ ant] [+ cor] property of distingtive feature if tha nasal sound [n] located at sound environment with [+ ant] property of distinctive feature. Key words: Phonological Processes (PP), Ikhfa’, Quranic Phonology, Generative Phonology, Distinctive Feature